The Use of Digital Learning Platform as Communication Media for Generation Z at PB. Soedirman Islamic High School, Jakarta - Iswadi, Iswadi; Iriansyah, Herinto Sidik; Erman Anom, Erman Anom (Didaktika Religia, 2024)
This study aims to evaluate the effectiveness of using digital learning platforms as communication media in Islamic education with a focus on Generation Z teachers at PB. Soedirman Islamic High School, Jakarta. This generation is known as digital natives who are highly adaptive to information technology. The research method used is a case study with a qualitative approach, involving interviews, participatory observation, and surveys. The results show that Generation Z teachers at PB. Soedirman Islamic High School, Jakarta feel comfortable and helped by the use of digital learning platforms for communication and learning. These platforms enable faster and more efficient communication. However, some challenges were also found, such as limitations in conveying messages clearly and the risk of information overload. Factors affecting the effectiveness of communication through digital platforms were identified, including Teachers' technological competence, platform design, organizational culture, and adequate training and support. This research is consistent with technology acceptance theory which states that perceived ease of use and usefulness have a significant effect on technology acceptance. The results of this study provide practical implications to optimize the use of digital learning platforms through continuous training, intuitive platform design, and digital culture support in the organization. Thus, digital platforms can improve the performance and job satisfaction of Generation Z teachers.